Advanced quantum mechanics : A practical guide - Nazarov, Yuli V.; Danon, Jeroen, 1977- (2013)
"An accessible introduction to advanced quantum theory, this graduate-level textbook focuses on its practical applications rather than mathematical technicalities. It treats real-life examples, from topics ranging from quantum transport to nanotechnology, to equip students with a toolbox of theoretical techniques"--
Includes index.
Keywords: Quantum theory -- Textbooks; SCIENCE / Quantum Theory